Pengaruh Kompetensi, Motivasi dan Kompensasi terhadap Kinerja Karyawan pada Perusahaan Klabers Studio Makassar - Muh. Zarkasyi Aziz; Achmad Gani; Masdar Mas’ud (Departement of Mathematics Education, 2023)
This study aims to obtain empirical evidence and analyze the effect of competence, motivation and compensation on employee performance at the Klabers Studio Makassar Company. This research uses the census method, the data used in this study are primary data in the form of questionnaires and secondary data. The research population is 31 employees within the scope of the Klabers Studio Makassar Company. While the sample in this study were 31 questionnaires distributed. The results showed that the competency and compensation variables had a positive and significant effect on employee performance. While the motivation variable has a positive and insignificant effect on employee performance at the Klabers Studio Makassar company